1999
DOI: 10.1021/bi990930z
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the C-Terminal Domain of Apolipoprotein A-I Impairs Cell Surface Binding and Lipid Efflux in Macrophage

Abstract: The contribution of the amphipathic alpha-helices of apoA-I toward lipid efflux from human skin fibroblasts and macrophage was examined. Four apoA-I mutants were designed, each by deletion of a pair of predicted adjacent helices. Three mutants lacked two consecutive central alpha-helices [Delta(100-143), Delta(122-165), and Delta(144-186)], whereas the final mutant lacked the C-terminal domain [Delta(187-243)]. When compared to recombinant wild-type apoA-I and mutants with central domain deletions, Delta(187-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
57
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 62 publications
(110 reference statements)
12
57
1
Order By: Relevance
“…3B). These results are generally consistent with those of an earlier study in which it was shown that neither C-terminal nor central domain mutations of apoA-I alter lipid efflux from fibroblasts (27). However, as was seen with J774 cells (Fig.…”
Section: Abca1-mediated Cholesterol and Phospholipid Efflux From J774supporting
confidence: 93%
See 4 more Smart Citations
“…3B). These results are generally consistent with those of an earlier study in which it was shown that neither C-terminal nor central domain mutations of apoA-I alter lipid efflux from fibroblasts (27). However, as was seen with J774 cells (Fig.…”
Section: Abca1-mediated Cholesterol and Phospholipid Efflux From J774supporting
confidence: 93%
“…It is apparent that deletion of the central domains (residues 44 -126 and 123-166) did not influence FC or PL efflux. These results agree with an earlier investigation in which it was shown that the elimination of the central domain of apoA-I had a minimal effect on ABCA1-dependent lipid efflux from THP-1 macrophages (27). Deletion of the N-terminal hydrophobic ␣-helix (residues 44 -65) and the N-terminal region (residues 1-43) led to a slight reduction in FC efflux relative to WT apoA-I (Fig.…”
Section: Abca1-mediated Cholesterol and Phospholipid Efflux From J774supporting
confidence: 92%
See 3 more Smart Citations